2014
DOI: 10.1371/journal.pgen.1004273
|View full text |Cite
|
Sign up to set email alerts
|

Folliculin Regulates Ampk-Dependent Autophagy and Metabolic Stress Survival

Abstract: Dysregulation of AMPK signaling has been implicated in many human diseases, which emphasizes the importance of characterizing AMPK regulators. The tumor suppressor FLCN, responsible for the Birt-Hogg Dubé renal neoplasia syndrome (BHD), is an AMPK-binding partner but the genetic and functional links between FLCN and AMPK have not been established. Strikingly, the majority of naturally occurring FLCN mutations predisposing to BHD are predicted to produce truncated proteins unable to bind AMPK, pointing to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 120 publications
(191 reference statements)
7
106
1
1
Order By: Relevance
“…These results prompted us to investigate the molecular signature of FLCN-null adipocytes responsible for the altered metabolic and lipid storage phenotype. FLCN interacts with AMPK and has been described as a negative regulator of AMPK signaling (Baba et al 2006;Possik et al 2014Possik et al , 2015Yan et al 2014). Indeed, we recently demonstrated that loss of FLCN constitutively activates AMPKα, which in turn leads to an elevation in PGC-1α levels and consequently induces mitochondrial biogenesis .…”
Section: Disruption Of Flcn Alters Adipocyte Physiologymentioning
confidence: 88%
See 2 more Smart Citations
“…These results prompted us to investigate the molecular signature of FLCN-null adipocytes responsible for the altered metabolic and lipid storage phenotype. FLCN interacts with AMPK and has been described as a negative regulator of AMPK signaling (Baba et al 2006;Possik et al 2014Possik et al , 2015Yan et al 2014). Indeed, we recently demonstrated that loss of FLCN constitutively activates AMPKα, which in turn leads to an elevation in PGC-1α levels and consequently induces mitochondrial biogenesis .…”
Section: Disruption Of Flcn Alters Adipocyte Physiologymentioning
confidence: 88%
“…FLCN has no significant sequence homology with any known protein and is highly conserved across species, suggesting an important biological role, as illustrated by the embryonic lethality of Flcn homozygous disruption in mice (Baba et al 2008;Chen et al 2008;Hudon et al 2010). FLCN functions as a repressor of the master energy sensor AMP-activated protein kinase (AMPK) via FLCN-interacting protein (FNIP) (Baba et al 2006(Baba et al , 2008Behrends et al 2010;Preston et al 2011;Possik et al 2014;Yan et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Since the chronic AMPK activation has been shown to lead to glycogen accumulation in multiple model systems, and because we have previously demonstrated that loss of flcn-1 chronically activates AMPK in C. elegans and in mammalian cells, 15 we hypothesized that the increased accumulation of glycogen in flcn-1 animals depends on AMPK. Indeed, we demonstrated using iodine staining, that AMPK is required for glycogen accumulation in both wild-type and flcn-1 animals.…”
Section: Flcn-1/ampk Regulates Glycogen Metabolism In C Elegansmentioning
confidence: 99%
“…[15][16][17] We also showed that the increased resistance to energy stresses is evolutionarily conserved and requires the 5'AMP-activated protein kinase (AMPK), a major regulator of cellular energy homeostasis and stress response. 15,17 In our recent work, we demonstrate an important role for FLCN-1/ AMPK in the regulation of resistance to hyperosmotic stress in C. elegans.…”
Section: Introductionmentioning
confidence: 99%